Coverage of development news in srilankan tamil news papers - Kiruththiga, T. (university of Jaffna, 2014)
The word development includes ideas such as economic, political, social, and cultural concerns. Development journalism is the profession of gathering, writing, editing, publishing, telecasting, or broadcasting information, facts and ideas about development activities. .Mass media have significant impact not only on a country's development but also individuals development.. This impact of media depends on the relevance of the content to be delivered. These contents are expected to comprise education, information, entertainment and edutainment that are vital for development. The most important reason to study development coverage in a newspaper is that they sheer ubiquity. After the completion of internal war need of development in the country should be improved This study compares the coverage of development issues in the selected newspapers in Srilanka..Newspapers' coverage of development issues by using mixed method: both quantitative and qualitative research methods with the aim of identifying the extent and quality of their coverage of development issues through. The main importance of this study is that it will help create awareness as to the extent to which the press gives for issues related to development. The focus of the study was on only one government newspaper and one private newspaper namely Thinakaran and Thinakkural and Veerakesari.(those are national dailies) and content and textual analysis as the research methodology. Development theory and framing theory gives theoretical foundation for this study.
Keywords: Communication; Srilanka; Development journalism; News coverage; Framing